Krishna
0

Step 1:  Identify the known parts of the problem.

                NOTE: \tan A = \cot B

                            Prove: A + B = 90\degree

Step 2: Make a use of the trigonometric ratios of complimentary angles.

            NOTE: We know \cot B = \tan (90\degree - B)............(1)


Step 3: Prove the required equation

              EXAMPLE: \tan A = \cot B


                                 \tan A = \tan (90\degree - B) [ \because Equation (1)]


                                Cancel the \tan on both sides


                                         A = 90\degree - B


                                         A + B = 90\degree

                                      Hence, proved